Factors Affecting Motivation to Choose TVET Teacher as a Career - Wahid, Wahidah; Rahim, Mohd Bekri (Research and Innovation in Technical and Vocational Education and Training, 2023)
The purpose of this research is to determine the factors that influence the motivation of choosing a career as a TVET teacher. This study also involved a comparison of career selection factors for male and female students. This study involved 301 undergraduate students of bachelor degree in vocational education from Universiti Tun Hussein Onn Malaysia. Data was collected through a questionnaire and were analyzed using SPSS software to obtain the mean score, frequency, and t-test statistics. The findings revealed that all factors such as interest, social influence, and social utility value have a high mean score value. In addition, only the social influence factor showed a significant difference in choosing a career as a TVET teacher for male and female students. This study is necessary to help the concerned parties explore the motivation factors that affect student to choose TVET teaching as their career. It is important to keep these future teachers motivated so that the TVET field can produce better-quality teachers in the future.